The Impact of Churg–Strauss Syndrome on Nasal Function and Quality of Life: An Underexplored Dimension - Luca Galassi; Federica Facchinetti (Sinusitis)
Eosinophilic Granulomatosis with Polyangiitis (EGPA)/Churg–Strauss syndrome is a systemic vasculitis that often causes chronic nasal dysfunction, including anosmia, nasal obstruction, and sinusitis. Anosmia, affecting up to 20% of EGPA patients, has a significant negative impact on quality of life (QoL). The loss of smell disrupts daily activities, reduces enjoyment of food, and impairs social interactions, leading to feelings of isolation, depression, and anxiety. These psychosocial consequences, combined with persistent physical symptoms, contribute to a marked decline in overall well-being and are among the strongest predictors of poor QoL in EGPA patients. Early diagnosis and intervention are essential to mitigate these effects and improve patient outcomes. A multidisciplinary approach that combines pharmacological treatment, surgical options, and psychosocial support is critical to managing both the physical and emotional challenges of nasal dysfunction in EGPA. However, further research is needed to explore long-term management strategies, optimize therapeutic approaches, and better address the complex interplay between physical symptoms and QoL in EGPA patients.